###### Advertisements

###### Advertisements

Simplify of the following:

`root(3)4 xx root(3)16`

###### Advertisements

#### Solution

We know that `root(n)a xx root(n)b = root(n)(ab)`.

We will use this property to simplify the expression `root(3)4 xx root(3)(16)`

`∴ root(3)(4) xx root(3)(16) = root(3)(64)`

`= root(3)(4^3)`

`= (4)^1`

= 4

Hence the value of the given expression is 4

#### APPEARS IN

#### RELATED QUESTIONS

Find the value to three places of decimals of the following. It is given that

`sqrt2 = 1.414`, `sqrt3 = 1.732`, `sqrt5 = 2.236` and `sqrt10 = 3.162`

`(2 + sqrt3)/3`

Find the value of `6/(sqrt5 - sqrt3)` it being given that `sqrt3 = 1.732` and `sqrt5 = 2.236`

Write the value of \[\left( 2 + \sqrt{3} \right) \left( 2 - \sqrt{3} \right) .\]

If\[\frac{\sqrt{3} - 1}{\sqrt{3} + 1} = x + y\sqrt{3},\] find the values of *x *and *y*.

If \[x = 3 + 2\sqrt{2}\],then find the value of \[\sqrt{x} - \frac{1}{\sqrt{x}}\].

`1/(sqrt(9) - sqrt(8))` is equal to ______.

Simplify the following:

`sqrt(45) - 3sqrt(20) + 4sqrt(5)`

Find the values of a and b in the following:

`(5 + 2sqrt(3))/(7 + 4sqrt(3)) = a - 6sqrt(3)`

Find the values of a and b in the following:

`(3 - sqrt(5))/(3 + 2sqrt(5)) = asqrt(5) - 19/11`

Find the values of a and b in the following:

`(sqrt(2) + sqrt(3))/(3sqrt(2) - 2sqrt(3)) = 2 - bsqrt(6)`